Energy Conservation and Pomeron Loops in High Energy Evolution - Gösta Gustafson (Brazilian Journal of Physics, 2007)
We present a formalism which modifies the Mueller Dipole Model such that it incorporates energymomentumconservation as well as important colour suppressed effects in the cascade evolution. The formalismis implemented in a Monte Carlo simulation program, and the results are compared to inclusive data from HERAand the Tevatron. We here find a generally very good agreement between our model and the experimental data.